Principals' Collaborative Roles as Leaders for Learning. Issue 2 (2nd April 2016) - Kitchen, Margaret; Gray, Susan; Jeurissen, Maree
ABSTRACT: This article draws on data from three multicultural New Zealand primary schools to reconceptualize principals' roles as leaders for learning. In doing so, the writers build on Sinnema and Robinson's (2012) article on goal setting in principal evaluation. Sinnema and Robinson found that even principals hand-picked for their experience fell short on goal setting. The principals in our study, unsettled by school and classroom conundrums, collaborated with their teachers to deliberately build their TESOL knowledge. We foreground the critical role of TESOL knowledge for principals in setting specific learning goals and valorize distributed leadership that forges non-traditional cross boundary links.